A Preliminary study on electrocardiogram response during pain induction - Bento, Ana (2022)
Pain is a complex phenomenon that arises from the interaction of multiple neuroanatomic and neurochemical systems with several cognitive and affective processes. Nowadays, the assessment of pain intensity still relies on the use of self-reports. However, recent research has shown a connection between the perception of pain and exacerbated stress response on the Autonomic Nervous System (ANS). The ANS, which is divided into the Parasympathetic Nervous System (PNS) and the Sympathetic Nervous System (SNS), functions as the subconscious regulator of the body. As a result, there has been increasing analysis of the autonomic reactivity with the objective to assess pain. The goal of this study was to explore and understand different responses in the electrocardiogram (ECG) signal when in the experience of pain. For this study, ECG was simultaneously recorded while a pain-inducing protocol (Cold Pressor Task - CPT) was implemented. Several features were extracted from the ECG to analyse differences related to pain induction tasks. The results obtained showed a statistically significant increase in the heart rate during the painful periods in comparison with non-painful periods. Additionally, heart rate variability features demonstrated a decrease in the PNS influence. These results are a step further in understanding the ECG response during the experience of pain, supporting the awareness and insights over physiological interactions within the pain experience.